Ensayos de contrarresto químico de las malezas de fríjol en Colombia : - Saldarriaga V., Alfredo; Benavides G., Marcial; Revelo P., Miguel (Ministerio de Ciencia Tecnología y Medio Ambiente - CITMA, 2018)
Fríjol-Phaseolus vulgaris